PERANAN WANITA/ISTRI NELAYAN DALAM USAHA MENGATASI PEREKONOMIAN KELUARGA PADA ERA NEW NORMAL DI KELURAHAN SINDULANG SATU KECAMATAN TUMINTING KOTA MANADO (Studi Kasus Kelompok Nelayan Daseng) - Soputan, Stevaldo J.M.; Manoppo, Victoria E.N.; Durand, Swenekhe S. (Universitas Sam Ratulangi, 2020)
AbstractThe purpose of this study is to analyze the economic condition of fishermen group households and to analyze the role of women in the household economy of fishermen groups during the Covid-19 pandemic and facing the new normal era in Sindulang Satu Village, Tuminting District, Manado City. The method used in this research is the case study method. The data analysis used in this research is quantitative analysis and qualitative analysis. The economic condition of the families of the Daseng fishing group in Sindulang Satu Village includes age, education and family dependents. The women / wives of the Daseng fishermen group are mostly in the productive age range so they are still active in carrying out income-generating activities and jobs, their education is dominated by elementary school graduates, while the dependents of the family have at most 1 - 3 dependents in the family. The role of women / wives in overcoming the family economy of fishermen groups during the Covid-19 pandemic and facing the new normal era, including domestic roles, namely cooking, cleaning and tidying houses, caring for children and helping husbands, active social roles in spiritual activities (mother worship) They also participate in arisan and PKK, and the productive role of women / wives of the daseng fishermen group is that they work as a washerman, open a small shop and sell. All the roles of the wife are very supportive of the economy of the Daseng group's fishing family.Keywords: Role of Women; Family Economy; Sindulang SatuÂ AbstrakTujuan penelitian ini ialah menganalisis keadaan perekonomian rumah tangga kelompok nelayan dan menganalisis sejauh mana peran perempuan dalam perekonomian rumah tangga kelompok nelayan dimasa pandemic covid-19 dan menghadapi era new normal di Kelurahan Sindulang Satu Kecamatan Tuminting Kota Manado. Metode yang digunakan dalam penelitian ini adalah metode studi kasus. Analisis data yang digunakan dalam penelitian ini adalah analisis kuantitatif dan analisis kualitatif.Keadaan perekonomian keluarga kelompok nelayan Daseng di Kelurahan Sindulang Satu meliputi keadaan umur, pendidikan dan tanggungan keluarga. Wanita/istri kelompok nelayan Daseng paling banyak dalam range umur produktif sehingga masih aktif dalam melakukan kegiatan dan pekerjaan yang menghasilkan pendapatan, pendidikan mereka didominasi oleh tamatan SD sedangkan tanggungan keluarga paling banyak memiliki 1 â€“ 3 orang tanggungan dalam keluarga. Peranan wanita/istri dalam mengatasi perekonomian keluarga kelompok nelayan dimasa pandemic covid-19 dan menghadapi era new normal, meliputi peran domestik yaitu memasak, membersihkan dan merapikan rumah, mengurus anak dan membantu suami, peran sosial dengan aktif dalam kegiatan kerohanian (ibadah kaum ibu) juga mengikuti arisan dan PKK, dan peran produktif wanita/istri kelompok nelayan daseng ada yang bekerja sebagai tukang cuci, membuka usaha warung dan berjualan. Semua peran istri sangat mendukung perekonomian keluarga nelayan kelompok Daseng.Kata Kunci: Peranan Wanita; Perekonomian Keluarga; Sindulang Satu